Anatomical variations and pathological changes in the hearts of free-ranging Eurasian lynx (Lynx lynx) in Finland - Kareinen, Ilona; Lavonen, Emilia; Viranta-Kovanen, Suvi; Holmala, Katja; Laakkonen, Juha
2020